Public Communication Strategy At Kominfo Department In Improving The Image Of The Coal District Government - Rismanto Manik; Muhammad Alfikri (IHSA Institute, 2022)
The goal of this research was to determine how the communication strategy implemented by Public Relations Diskominfo Batu Bara Regency helped to improve the image of the Batu Bara Regency government. This is an example of qualitative research. During the research, it was discovered that the Batu Bara Regency government's Public Relations strategy included collaborating with print and electronic media as media in reporting. If there is negative news about the Batu Bara Regency government, the steps to take are to clarify the negative information and increase the dissemination of positive information to the Batu Bara Regency government, utilizing information technology through official information channels in cyberspace for media dissemination of information by good framing and agenda setting in order to form a positive image of the Batu Bara district government so that it can be maintained in providing services.